LncRNA ARGI Contributes to Virus‐Induced Pancreatic β Cell Inflammation Through Transcriptional Activation of IFN‐Stimulated Genes - González‐Moro, Itziar; Garcia‐Etxebarria, Koldo; Mendoza, Luis Manuel; Fernández‐Jiménez, Nora; Mentxaka, Jon; Olazagoitia‐Garmendia, Ane; Arroyo, María Nicol; Sawatani, Toshiaki; Moreno‐Castro, Cristina; Vinci, Chiara; Op de Beek, Anne; Cnop, Miriam; et al. (Advanced science, 2023)
Type 1 diabetes (T1D) is a complex autoimmune disease that develops in genetically susceptible individuals. Most T1D‐associated single nucleotide polymorphisms (SNPs) are located in non‐coding regions of the human genome. Interestingly, SNPs in long non‐coding RNAs (lncRNAs) may result in the disruption of their secondary structure, affecting their function, and in turn, the expression of potentially pathogenic pathways. In the present work, the function of a virus‐induced T1D‐associated lncRNA named ARGI (Antiviral Response Gene Inducer) is characterized. Upon a viral insult, ARGI is upregulated in the nuclei of pancreatic β cells and binds to CTCF to interact with the promoter and enhancer regions of IFNβ and interferon‐stimulated genes, promoting their transcriptional activation in an allele‐specific manner. The presence of the T1D risk allele in ARGI induces a change in its secondary structure. Interestingly, the T1D risk genotype induces hyperactivation of type I IFN response in pancreatic β cells, an expression signature that is present in the pancreas of T1D patients. These data shed light on the molecular mechanisms by which T1D‐related SNPs in lncRNAs influence pathogenesis at the pancreatic β cell level and opens the door for the development of therapeutic strategies based on lncRNA modulation to delay or avoid pancreatic β cell inflammation in T1D. Long non‐coding RNAs (lncRNAs) are emerging as regulators for several molecular processes that are important for human diseases. Herein, the function of a type 1 diabetes (T1D)‐associated lncRNA named ARGI is described. ARGI modulates the transcription of virus‐induced IFNβ and interfer on stimulated genes (ISGs) in pancreatic β cells in an allele‐specific manner.